APPLICATION OF THE DAMPSTER SHAFER METHOD TO DIAGNOSE MALNUTRITION IN TODDLERS - Nuraisana, Nuraisana; Sijabat , Petti Indrayati; Harun , Muhammad (Sean Institute, 2022)
The toddler period is a golden period that must be put to good use by parents. The golden period is a determinant for the growth and development of children. Malnutrition in children can lead to various diseases that can hinder the growth and development of children. Posyandu Desa Tanjung Garbus Kampung is an integrated service center that provides public health services. Lack of knowledge and experience of Posyandu health workers in Tanjung Garbus Village Village is one of the problems in diagnosing malnutrition in toddlers because it is only based on the toddler's weight and height. The dempster shafer method is a method in expert systems that applies a mathematical theory for proof based on a function of belief and reasonable reasoning (belief function and reasonable thinking), which is used to combine separate pieces of information (evidence) to calculate the likelihood of an event. With this system, it is expected to be able to diagnose malnutrition in toddlers quickly and efficiently.